Isoladores para alta tensão: estudos sobre poluição artificial para ensaios elétricos de suportabilidade e para auxílio a predição de intervenções - Monteiro, Alison Baena de Oliveira (2024)
The use of insulators in the Power Electric System (PES) is essential to ensure the functionality of these systems across various climates, environmental conditions, and biomes, playing a fundamental role both electrically and mechanically. Insulation failures, often caused by local pollution accumulating on insulators, are among the main factors leading to partial or permanent system faults. Deposits of materials such as salt and insoluble particles can generate leakage currents, surface discharges, material degradation, and disruptive discharges (flashovers), compromising the integrity of the PES. The origin of these deposits can be natural or anthropogenic, requiring that the design and selection of insulators consider the environmental conditions and adequate electrical withstand capacity for the installation region. Pollution analysis is performed by collecting and studying the deposits accumulated on the insulators, determining the intensity and severity through the amount of soluble and insoluble particles. This study presents the development of artificial pollution methods to condition porcelain or glass insulators, accurately replicating the pollution levels defined by the ABNT IEC 60815 standard. The research included impedance measurements using frequency sweep spectroscopy and surface resistivity measurements under controlled temperature and humidity conditions in a climate chamber. The results demonstrated the relationship between pollution levels, temperature, and humidity, culminating in the creation of surface resistivity curves for different climates and the development of a fuzzy scale to indicate instant pollution intensity. In summary, the study significantly contributes by providing a robust artificial pollution methodology applicable to electrical testing and by offering data that support the development of instant measurement techniques, enabling predictive interventions in PES equipment and strengthening the reliability and durability of power systems.